A novel carbon dioxide capture system for a cement plant based on waste heat utilization. (1st April 2022) - Wang, Yihan; Chen, Heng; Wang, Huating; Xu, Gang; Lei, Jing; Huang, Qilong; Liu, Tong; Li, Qiubai
Graphical abstract: Highlights: Cement plants waste heat is further utilized by powering its decarbonization. Recovery of waste heat from the decarbonization process for heating or cooling. Revenue compensates capture cost under an appropriate decarbonization rate. Integration and optimization result in the cost of CO2 avoided is 46.31 $/t CO2 . Abstract: A novel carbon dioxide capture system that combines cooling, heating and power (CCHP) based on a cement plant has been developed and evaluated. The proposed integration is realized by recovering the waste heat of cement flue gas to produce electricity for decarburization or sale. The novel system can reduce the expensive external energy consumption for decarbonization by fully utilizing the heat itself. The heat loss of the CO2 capture process is utilized to supply heat directly or provide cooling by an NH3 -H2 O absorption refrigeration system. An appropriate decarbonization rate (18.89 %) is determined when the income just as much as possible compensates for the cost of decarbonization. The coupled system is assessed from thermodynamic and economic perspectives to exhibit its feasibility. Under the heating mode, 5.52 MW energy is recovered from the decarbonization heat loss. Meanwhile, a total system efficiency of 10.28 % and a total exergy efficiency of 8.18 % can be achieved. Both metrics are superior to the cooling mode, in which 3.66 MW energy is taken into the absorption refrigeration system for suppling 0.82 MW of cooling. Finally, the annual income achieves 3287.07 k$ while the COA as low as 46.31 $/t CO2 under this decarbonization rate.